Flavonoids from sour jujube leaves: Ultrasound-assisted extraction, UPLC-QQQ-MS/MS quantification, and ameliorative effect on DSS-induced ulcerative colitis in mice - Hongke Wei; Xiaomin Wang; Jiaqi Wang; Shijie Ren; Luis A.J. Mur; Dong Lu; Duo Cao (Ultrasonics Sonochemistry)
To valorize sour jujube (Ziziphus acidojujuba) leaves, this work focused on the extraction, quantification, and bioactivity assessment of flavonoids. First, ultrasound-assisted extraction (UAE) was employed to extract total flavonoids from sour jujube leaves (SJL-TF), with the procedure optimized through single-factor design and response surface methodology (RSM). SJL-TF yield reached 48.47 ± 0.36 mg/g under optimal circumstances, which included 61 % ethanol as extraction medium, an ultrasound power of 300 W, an extraction time of 33 min, and a liquid–solid ratio of 16 mL/g, showing higher extraction efficiency in comparison to the traditional Soxhlet extraction method. Scanning electron microscopy (SEM) analysis indicated that ultrasound treatment severely damaged the structural integrity of sour jujube leaves, which was more conducive to improving the SJL-TF yield. Then, polyamide resin chromatography was used to purify the crude SJL-TF extracts, increasing the SJL-TF purity by 3.2-fold to 74.58 ± 0.63 %. By developing and validating a UPLC-QQQ-MS/MS method, ten main flavonoids in SJL-TF extracts, including catechin, rutin, isoquercetin, narirutin, nicotiflorin, quercitrin, phlorizin, luteolin, quercetin, and apigenin, were successfully detected concurrently for quality control purposes. Furthermore, the purified SJL-TF showed a strong ameliorative effect on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in mice, as evidenced by significant mitigation of colonic inflammation and pathological damage. Thus, this work will contribute to improving the application of sour jujube leaves, especially in the pharmaceutical sector.